Therapeutic effects of Poncirus fructus on colonic dysfunction and visceral pain in a zymosan-induced irritable bowel syndrome mouse model through interstitial cells of Cajal and ion channel modulation - Choi, Na Ri; Ko, Seok-Jae; Choi, Woo-Gyun; Jung, Daehwa; Kim, Sang Chan; Lim, Dong Wook; Kim, Yun Tai; Woo, Joo Han; Park, Jae-Woo; Kim, Byung Joo (Frontiers in Pharmacology, 2025)
PurposeIrritable bowel syndrome (IBS) is a prevalent gastrointestinal disorder with few effective long-term treatments. This study investigated the therapeutic potential of Poncirus fructus extract (PFE) for IBS-like symptoms, focusing on interstitial cells of Cajal (ICCs), visceral pain–related ion channels, inflammation, and gut microbiota.MethodsA zymosan-induced colitis mouse model was employed to mimic IBS-associated inflammation and pain. Electrophysiological recordings were performed in murine colonic ICCs and HEK293T cells overexpressing TRPV1, TRPV4, TRPA1, NaV1.5, or NaV1.7 channels. Additional analyses included histology, TNF-α measurement, behavioral pain assessments, and gut microbiota profiling.ResultsPFE depolarized ICC pacemaker potentials in a dose-dependent manner through HCN channel activation and M3 muscarinic receptor–mediated PLC-PKC signaling involving p38 MAPK and JNK pathways. In vivo, PFE improved colon length, reduced tissue inflammation and damage, lowered TNF-α levels, and alleviated pain-related behaviors in zymosan-treated mice. Gut microbiota analysis revealed increased abundance of Lachnospiraceae following PFE treatment. Electrophysiology showed that PFE inhibited TRPV1 and NaV1.5/1.7 currents, enhanced TRPV4 current, and had no effect on TRPA1 current.ConclusionPFE exerts multi-target effects by modulating ICC activity, suppressing inflammation, and regulating key ion channels involved in visceral pain. These findings suggest that PFE has therapeutic potential for the management of IBS symptoms.